THE EFFECT OF THE RADEC LEARNING MODEL ASSISTED BY E-MODULES ON CULTURAL DIVERSITY ON THE MULTICULTURAL UNDERSTANDING AND TOLERANT ATTITUDES - Ni Made Winursiti; Wahyu Sopandi; Encep Supriatna (Universitas Majalengka, 2026)
This study aims to describe the implementation of the RADEC learning model (LM) assisted by e-modules on cultural diversity and to examine its effect on the multicultural understanding and tolerant attitudes attitudes of fourth-grade elementary school students. It also compares the improvement of both variables between students taught using the RADEC LM assisted by e-modules on cultural diversity and those taught using the expository learning model. The study employs a quasi-experimental approach with a Non-equivalent Pretest and Posttest Control Group Design. The participants consist of fourth-grade students from two elementary schools in Waringinkurung District, Serang Regency, Banten Province. Data are collected through observations, questionnaires, and essay tests, and are analyzed using paired-sample t-tests and independent-sample t-tests with the assistance of IBM SPSS Statistics version 29. The results show that the implementation of the RADEC LM assisted by e-modules on cultural diversity is carried out effectively in the experimental group. The paired-sample t-test indicates significant effects on both multicultural understanding and tolerant attitudes attitudes, with significance values of 0.000 (Sig. < 0.05). The independent-sample t-test also demonstrates significant differences between the experimental and control groups in multicultural understanding (Sig. = 0.000 for posttest; Sig. < 0.05 for n-gain) and tolerant attitudes attitudes (Sig. = 0.000 for posttest; Sig. < 0.05 for n-gain). Furthermore, the n-gain scores of the experimental group fall into the high category for multicultural understanding (0.79) and tolerant attitudes attitudes (0.90), while the control group scores fall into the moderate category. These findings indicate that the RADEC LM assisted by e-modules on cultural diversity is effective in enhancing students’ multicultural understanding and tolerant attitudes attitudes. The study implies that teachers can employ this model to strengthen literacy in reading and writing as well as digital technology skills.